Allometry of reaching and contact structures in Kukulcania hibernalis (Araneae: Filistatidae). Issue 6 (11th September 2019) - Barrantes, Gilbert; Madrigal‐Brenes, Ruth
Abstract: Large part of the morphological diversity observed across taxa is attributed to the effect of sexual selection; and the static allometry of these structures vary largely from highly positive to negative, depending on their function, and position on the animal's body. In arthropods, information of how sexually selected contact and reaching male structures use during courtship scale on body size is scarce. We tested two complementary hypotheses: the reaching structure hypothesis and the contact‐function hypothesis, in the spider Kukulcania hibernalis . We used the length of the proximal segments of the male pedipalp to test the reaching structure hypothesis, and claw features to test the contact‐function hypothesis. Our results support both hypotheses. Small males have disproportionally longer pedipalps (highly negative allometry) than large males, increasing the probability of small‐bodied males to inseminate even large females. We also found that both distal contact and noncontact homologous structures scaled shallow (slope < 1) on body size, but allometry was significantly shallower for contact than for noncontact distal structures, providing support to the contact‐function hypothesis, and allowing teasing apart the effect of sexual selection on distal contact structures with dual functions. Abstract : The paper includes five figures. Figure 1 consists of two pictures showing part of the courtship behavior of Kukulcania hibernalis, while figure 2 shows the features of the claws that were included in the analyses. Figures 3 and 4 display the scaling of different appendages of females and males on body size. Figure 5 shows the proportion of protruding teeth for each leg of males and females. HIGHLIGHTS: We tested the effect of sexual selection on reaching and distal contact devices. Small males have disproportionally longer pedipalps to reach the copulatory opening of females. We teased apart the effect of a dual function effect on a distal contact device.